MORPHOLOGICAL AND MECHANICAL PROPERTIES OF POLYPROPYLENE/EPOXIDIZED NATURAL RUBBER THERMOPLASTIC VULCANIZATES TREATED WITH MALEIC ANHYDRIDE-GRAFTED POLYPROPYLENE - Mohamad, Noraiham; Zainol, Nur Sharafina; YAAKOB, MOHD YUHAZRI; ABD RAZAK , JEEFFERIE (UMP Publisher, 2013)
This research is to investigate the morphological and mechanical properties of thermoplastic vulcanizates, polypropylene/ epoxidized natural rubber (PP/ENR) when treated with maleic anhydride-grafted polypropylene (Mah-PP). The PP/ENR thermoplastic vulcanizated was prepared through 2 stages melt compounding method using an internal mixer at specified temperature and time. Then it was mixed and dynamically vulcanized using a semi-EV sulfur curing system in an internal mixer at170oC for 10 minutes. Mah-PP was varied from 5, 10 to 15 % in the samples. Tensile and hardness testing were performed on the sample to characterize the mechanical properties of PP/ENR vulcanizates. The morphology was observed under a Scanning Electron Microscope (SEM) at magnification of 500x and 2000x. 50/50 PP/ENR vulcanizates showed improvement up to 400% elongation at break if compared to pure PP. In contrast, tensile strength and hardness decrease as the amount of PP decrease. However, the tensile properties of vulcanizates improved with the addition of Mah-PP compatibilizer into the blend during compounding process. It was contributed by enhancement in miscibility between thermoplastic and rubber molecules with the presence of compatibilizer. Morphological observation on vulcanizates showed two phase system ENR phase were dispersed as domains in a continuous thermoplastic matrix. The domain size of dispersed ENR particles decreased with the addition of compatibilizer. As conclusion, the addition of Mah-PP improved the tensile strength and Young’s modulus of the thermoplastics matrix. Morphologies of tensile fractured surfaces of treated PP/ENR blends revealed better interaction between PP and ENR with the presence of Mah-PP.